DEVELOPMENT OF STEM-PjBL BASED WORKSHEET INTEGRATED ENTREPRENEUR CHARACTERISTICS TO IMPROVE CREATIVE THINKING SKILLS - Yulia Pratiwi, Inke; Sutrisno, Sutrisno; Anggeraini, Evita (LPPM Univ. Ibn Khaldun Bogor, 2023)
The purpose of this development research is to produce an integrated STEM-PjBL-based worksheet product with entrepreneurial characteristics oriented towards students' creative thinking skills in the subject of energy in life. This research is a type of research and development using the 4D model which consists of 4 mutually continuous stages, namely: define, design, develop, and disseminate. STEM-PjBL based worksheet has been developed and validated by material expert validators and media expert validators. Then it was tested on class VII students at SMP N 1 Jambi City. The results of the analysis of science teachers' responses to worksheet obtained an average percentage score of 89.58% which was categorized as